Evaluation of the Use of Antibiotics in the COVID-19 Ward at A North Jakarta Hospital - Arrang, Sherly Tandi; Buntoro, Leonardo; Notario, Dion (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2023)
The misuse of antibiotics can lead to antibiotic drug resistance, which can increase morbidity and mortality. In order to stop the emergence of antibiotic drug resistance, the WHO recommends routinely assessing the usage of antibiotics. When the COVID-19 epidemic broke out, antibiotic consumption significantly increased compared to the prior year. The panic buying phenomenon also appeared during the COVID-19 pandemic. As a result of this circumstance, medications like antibiotics become rare. The abuse of antibiotics during the COVID-19 pandemic may have contributed to the spread of antibiotic resistance more frequently. This study was conducted to evaluate and describe the use of antibiotic drugs in COVID-19 ward patients at a North Jakarta regional hospital for the period April 2020 – April 2021. This study was an observational study design. The Gyssens method and the Anatomical Therapeutic Chemical/Defined Daily Doses (ATC/DDD) methodology, respectively, evaluate the effectiveness of antibiotic use on a quantitative and qualitative level. There were 24 different types of antibiotics used, and 161 respondents all met the criterion for inclusion. The most widely used antibiotic was azithromycin, with a DDD/100 patient days value of 25.15. According to Gyssen’s evaluation, 92.6% of antibiotic usage was rational and 7.4% was irrational.